Perbandingan Sistem Pendidikan Turki Dan Indonesia - Novita Sari; Komarudin Sassi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This article discusses the comparison of education in two countries, namely Turkey and Indonesia, where the majority of the population is Muslim. As well as explaining the education system in elementary schools, middle schools and universities. Apart from that, this article examines education system policies, education management and education curriculum. These two countries have several similarities, each country implements a compulsory education policy and divides education levels into three levels. Another similarity is that students have a high interest in continuing their studies in foreign universities. The approach used by the author in conducting this research is a descriptive qualitative method by searching various data from documents and literature in the form of; literature, articles, books, journals, other supporting websites.